PENILAIAN MASYARAKAT TERHADAP PROGRAM PENDIDIKAN TPQ NURUS SHOLAH DI BANGKALAN MADURA - Moh. Ilyas (Universitas Kiai Abdullah Faqih Gresik, 2024)
Abstract: The purpose of this study is to determine the extent to which the community in Bangkalan Madura's Al-Quran Education Park (TPQ) Nurus Sholah, in the Pejagan hamlet, views education. This study uses a qualitative methodology that combines documentation, interviews, and direct observation to comprehend social processes from the viewpoint of the participants. Because of its significance to the issue of community involvement in the advancement of children's education in non-formal educational institutions, the village of Pejagan was selected. According to the analysis's findings, the Pejagan community has a highly positive opinion of TPQ Nurus Sholah's educational program, particularly when it comes to its academic, social, and economic components. A key element in TPQ Nurus Sholah's success is its involvement in social and economic activities, solidarity within the community, and active support from different societal strata. But in order to raise the standard of instruction at TPQ Nurus Sholah, a number of issues must be resolved. For example, parents' busy schedules often prevent them from seeing the value of teaching their children the Quran from a young age. This study offers a thorough analysis of the dynamics of community support for non-formal educational institutions, specifically TPQ. The results bolster TPQ Nurus Sholah's influence in forming the moral and spiritual values of the next generation and provide a framework for future strategy development. Keywords: education, community involvement, and community perspective